The innovation system vs. cluster process: common contributive elements towards regional development - George Ramos; Domingos Santos (European Regional Science Association (ERSA), 2004)
Recent approaches to the study of innovations enhance some similar aspects of the innovation process in knowledge-based economies: (i) the systemic and interrelated nature of innovation and (ii) its geographic and inter-economic activities density of networking. One perspective is linked to the innovation systems approach at the national, regional and local level. What we know so far is that the most specialized forms of knowledge are becoming a short lived resource, in face of the (increasingly) fast changes that are occurring in the global economy; it's the ability to learn permanently and to adapt to this fast changing scenario that determines the innovative performance of firms, regions and countries. Another approach is to be found in the research on cluster development, where proximity and interrelated technical/technological linkage are the main features to take under consideration. Although these two approaches operate at slightly different spatial scale of analysis, they both allow the identification of a set of key factors that contribute to understand the way in which institutions and actors, considering the innovation system or the cluster process, participate in the innovation atmosphere and in the economic growth. Nevertheless, both approaches show the same limitation: they tend to focalise into the descriptive and analytical level, disregarding the explanatory level. Local and regional authorities are, mainly, interested in the process of cluster intensification in the local and regional economies context. This feature stress out one other controversy level: are the “hard” location factors (the concrete tangible location factors) more important than the “soft” location factors (qualitative, intangible factors) or vice-versa? This paper aims to explore the current knowledge about this process and to open some fields of future research.
Keywords: 330